2012
DOI: 10.1111/j.1439-0396.2012.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intake of linoleic acid and α‐linolenic acid levels on conversion into long‐chain polyunsaturated fatty acids in backfat and in intramuscular fat of growing pigs

Abstract: A study was conducted to determine the effect of two levels of linoleic acid (LA) intake at either high or low α-linolenic acid (ALA) intake on their conversion and subsequent deposition into long-chain (20-22 C-atoms) polyunsaturated fatty acids (LC PUFA) in muscle and backfat in growing pigs. In a 2 × 2 factorial arrangement, 32 gilts from 8 litters were assigned to one of four dietary treatments, varying in LA and ALA intakes. Low ALA and LA intakes were 0.15 and 1.31 g/(kg BW(0.75) /day), respectively, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In the current study, a similar level of enrichment was achieved after 31 days of supplementation with 1% AURA. Vossen et al [ 12 ], who investigated the effects of dietary supplementation with Schizochytrium (0.3% to 2.2% algae) for a period of 45 days found similar levels of enrichment to the current study, reporting 10 to 20 mg of DHA/100 g of pork longissimus thoracis . Sardi et al [ 11 ] also used Schizochytrium to supplement the diet of pigs and demonstrated increases in the DHA content of LL from 100% to 250%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the current study, a similar level of enrichment was achieved after 31 days of supplementation with 1% AURA. Vossen et al [ 12 ], who investigated the effects of dietary supplementation with Schizochytrium (0.3% to 2.2% algae) for a period of 45 days found similar levels of enrichment to the current study, reporting 10 to 20 mg of DHA/100 g of pork longissimus thoracis . Sardi et al [ 11 ] also used Schizochytrium to supplement the diet of pigs and demonstrated increases in the DHA content of LL from 100% to 250%.…”
Section: Discussionsupporting
confidence: 84%
“…However, it is unlikely that these are the only causes for the increased concentration of EPA in the LL. Vossen et al [ 12 ], also observed an increase in the concentration of EPA that could not have come directly from the diet. The authors suggested that higher EPA concentrations in algae supplemented pigs could be attributed to DHA retro-conversion, a minor metabolic pathway which involves one cycle of β-oxidation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we analyzed the FA profile of skeletal muscle from growing animals and found a surprising enrichment in docosahexaenoic acid (DHA, 22:6n-3) over 1 year, whereas the n-3 precursor supply was lowered in the diet over time. This accumulation may be inherent to the muscular incorporation of long-chain PUFA, since 18:3n-3 would not be converted into derivatives such as DHA in such tissue [39,40]. In addition, different studies have shown the beneficial effects of dietary DHA on muscle physiology.…”
Section: Discussionmentioning
confidence: 97%
“…As a result, the animal products are now much higher in n-6 PUFAs and lower in n-3 PUFAs. Smink et al (2013) suppressed the effect of ALA intake on n-3 LC-PUFAs by LA intake and suppressed the concentration of n-6 LC-PUFAs in blood plasma by dietary ALA. They found that the inhibiting effect of ALA in blood ARA, at equal increasing intakes, was stronger than the stimulating effect of LA as a precursor.…”
mentioning
confidence: 99%